A Learning Organization in Practice: Service Development in Care Work - Amble, Nina (Nordic Journal of Working Life Studies, 2017)
The title is partly borrowed from David (P. G.) Herbst’s 1993a: A Learning Organization in Practice. Herbst’s text has an empirical basis in a matrix, ship organization, while this article stems from a project in a public care, 24–7 continuous work similar to the ship organization. An interactive research process, combining focus groups, interviews, participation in meetings and seminars supported this process. The purpose here is not to report the research process itself, but to combine concepts, some from the Industrial Democracy tradition, and use them as an analytical tool to clarify how, under certain circumstances, the introduction of a new service was implemented in a jointly developed, interdisciplinary process of employees.